Integrative dereplication and molecular networking reveal potential antimicrobial agents in Kielmeyera coriacea Mart. - Coqueiro, Aline; Wakui, Vinicius Galvão; Pilon, Alan C. [UNESP]; Castilho, Nathália S.; Costa, Eliângela C. C.; Monteiro, Afif F. [UNESP]; Anjos, Charlene S. dos; Leandro, Luis Fernando; Martins, Carlos Henrique Gomes; Pasqualotto Severino, Vanessa G. (Taylor & Francis, 2025)
Kielmeyera coriacea Mart., native to Brazilian Cerrado, is traditionally used in folk medicine. The MIC against bacteria and yeasts was determined for the ethanolic extracts of roots, outer bark, leaves, and fruits. A dereplication strategy via HPLC-ESI-HRMS/MS and GNPS was used to identify known compounds and highlight potential compounds responsible for the activities. The root extract exhibited the most promising activity against a range of bacteria and fungi. This extract was selected for further fractionation, yielding n-hexane, ethyl acetate, and hydroalcoholic fractions. These were evaluated against the same microbial strains. Subsequent chromatographic analysis and bioactivity tests identified two highly active subfractions from the n-hexane and hydroalcoholic fractions. Detailed analysis using standards and databases (GNPS and Scifinder) led to the annotation of three xanthones (kielcorin, and its hydroxy- and methoxy- derivatives), three glycosylated flavonoids, and two acylphoroglucinol derivatives (garcinielliptone D e A).
Keywords: acylphoroglucinol; antibacterial; antifungal; dereplication; Kielmeyera coriacea